Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1093/emboj/20.6.1289
|View full text |Cite
|
Sign up to set email alerts
|

Male germ cells and photoreceptors, both dependent on close cell–cell interactions, degenerate upon ClC-2 Cl− channel disruption

Abstract: The functions of some CLC Cl(-) channels are evident from human diseases that result from their mutations, but the role of the broadly expressed ClC-2 Cl(-) channel is less clear. Several important functions have been attributed to ClC-2, but contrary to these expectations ClC-2-deficient mice lacked overt abnormalities except for a severe degeneration of the retina and the testes, which led to selective male infertility. Seminiferous tubules did not develop lumina and germ cells failed to complete meiosis. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
317
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(329 citation statements)
references
References 61 publications
11
317
1
Order By: Relevance
“…Gain of function mutations in this gene have been shown to be responsible for hereditary thrombocythaemia [8,9]. CLCN2, a gene for which the mice knock-out model of its homolog demonstrates leukoencephalopathy [10] and degeneration of retinal and testicular cells, leading to male infertility is present in the deleted region [11]. The CLCN2 rat homolog is expressed in fetal lung and its expression rapidly decreases after birth; therefore its deficiency may be related to the neonatal respiratory distress [12] and testicular anomalies observed in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gain of function mutations in this gene have been shown to be responsible for hereditary thrombocythaemia [8,9]. CLCN2, a gene for which the mice knock-out model of its homolog demonstrates leukoencephalopathy [10] and degeneration of retinal and testicular cells, leading to male infertility is present in the deleted region [11]. The CLCN2 rat homolog is expressed in fetal lung and its expression rapidly decreases after birth; therefore its deficiency may be related to the neonatal respiratory distress [12] and testicular anomalies observed in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…ClC-2 knockout mice do not have epilepsy. 172 In humans, however, ClC-2 mutations cosegregated in three families with various idiopathic generalized epilepsy syndromes, including JME, juvenile absence epilepsy, CAE, and epilepsy with grand mal seizures on awakening (EGMA). 173 Functional studies in transfected cells suggest that the mutations cause a loss of function.…”
Section: Voltage-gated Chloride Channelsmentioning
confidence: 99%
“…Many physiological functions have been postulated for ClC-2 (9), but blindness and male infertility were, surprisingly, the only phenotypes noted in ClC-2 knock-out mouse models (24,25). An impaired transepithelial transport across the retinal pigment epithelium and Sertoli cells was hypothesized as the mechanism underlying the retinal and testicular degeneration, respectively (24). Indeed, Ussing chamber experiments revealed that transepithelial voltage and resistance were reduced in the pigment epithelium of Clcn2 Ϫ/Ϫ mice (24).…”
mentioning
confidence: 99%
“…An impaired transepithelial transport across the retinal pigment epithelium and Sertoli cells was hypothesized as the mechanism underlying the retinal and testicular degeneration, respectively (24). Indeed, Ussing chamber experiments revealed that transepithelial voltage and resistance were reduced in the pigment epithelium of Clcn2 Ϫ/Ϫ mice (24).…”
mentioning
confidence: 99%